2019
DOI: 10.31850/makes.v2i3.192
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Kunjungan Balita Ke Posyandu Di Wilayah Kerja Puskesmas Mangkoso Kabupaten Barru

Abstract: Posyandu merupakan wadah untuk mendapatkan pelayanan dasarterutama dilaksanakan oleh kader yang telah dilatih dibidang kesehatan dan KB, dimana anggotanya berasal dari PKK, tokoh masyarakat dan pemudi. Kader kesehatan merupakan perwujudan peran serta aktif masyarakat dalam pelayanan terpadu, dengan adanya kader yang dipilih oleh masyarakat, kegiatan diprioritaskan pada lima program dan mendapat bantuan dari petugas kesehatan terutama pada kegiatan yang mereka tidak kompeten memberikannya. Penelitian ini bertuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…From the results of the statistical test (chi square), a p-value of 0.000 was obtained, where the value was <0.05, which means that Ha was accepted, so it can be concluded that there is a relationship between distance and baduta visits to the health center. This is in line with research conducted by Yusuf & Rusman (2019) which showed the results that there was a relationship between distance between residence and visits by toddlers to posyandu in the Mangkoso Community Health Center working area in 2017 with p=value 0.004. These results are also in accordance with the opinion of Lawrence Green in Notoatmodjo (2018) who states that the availability of health facilities is one of the enabling factors that can shape health behavior.…”
Section: Bivariate Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…From the results of the statistical test (chi square), a p-value of 0.000 was obtained, where the value was <0.05, which means that Ha was accepted, so it can be concluded that there is a relationship between distance and baduta visits to the health center. This is in line with research conducted by Yusuf & Rusman (2019) which showed the results that there was a relationship between distance between residence and visits by toddlers to posyandu in the Mangkoso Community Health Center working area in 2017 with p=value 0.004. These results are also in accordance with the opinion of Lawrence Green in Notoatmodjo (2018) who states that the availability of health facilities is one of the enabling factors that can shape health behavior.…”
Section: Bivariate Analysissupporting
confidence: 90%
“…The results showed that there was a relationship between attitude and the visit of the ambassador. The results of this research are in accordance with research conducted by Yusuf & Rusman (2019) which shows that there is a relationship between distance between residence and visits by toddlers to posyandu. Based on 3. it is known that the majority of female baduta respondents, namely 48 people (60%) have poor knowledge, and there are 32 people (40%) who have good knowledge.…”
Section: Univariate Analysissupporting
confidence: 90%
“…Salah satu indikasi pemanfaatan pelayanan kesehatan adalah keaktifan kedatangan masyarakat ke pusat pelayanan tersebut yang dalam hal ini spesifik kepada pemanfaatan pelayanan kesehatan posyandu. Meningkatkan kualitas pelayanan kesehatan di posyandu diperlukan intervensi dari pembina posyandu yaitu puskesmas untuk menjamin pelaksanaan penyuluhan pada ibu bayi dan ibu balita dapat tercapai sesuai dengan target (Satriani, 2019).…”
Section: Pendahuluanunclassified
“…Partisipasi masyarakat melalui kunjungan ibu balita ke posyandu rendah dapat disebabkan karena pengetahuan orang tua tentang pentingnya posyandu untuk balita diimunisasi atau ditimbang tidak banyak memahami apa itu posyandu (Satriani et al, 2019). Pengetahuan dengan kunjungan ibu balita ke posyandu untuk menimbang anaknya sangat berpengaruh terhadap keaktifannya untuk berpartisipasi kegiatan posyandu khususnya D/S (Munawarah et al, 2022).…”
Section: Gambar 3 Dokumentasi Kegiatanunclassified